At the origins of Christian worship the context and character of earliest Christian devotion - Hurtado, Larry W.; Didsbury lectures, 1999. (Carlisle, UK Paternoster, 1999)
Includes bibliographical references.
The Didsbury lectures are delivered annually at the Nazarene Theological College, Manchester, by leading scholars from a variety of schools of thought.
Keywords: Worship -- history